Letters of Alliance and an Alliance of Letters: Aeneas Silvius Piccolomini, Juan de Carvajal, and the Conciliar Crisis. - O'BRIEN, EMILY (Renaissance & Reformation / Renaissance et Réforme, 2019)
This contribution charts a new pathway in the correspondence between Aeneas Silvius Piccolomini (1405-64) and Juan de Carvajal (1399Î-1469) by focusing primarily on the relationship between the two men. It argues that each sought to adjust their relationship to fit the political demands of the moment, and that they used it, or tried to use it, as a tool to navigate and even resolve the conciliar crisis. This article enriches our understanding of a critical moment in church history, sharpens our grasp of the roles of both Piccolomini and Carvajal, and suggests new ways that humanism contributed to the fifteenth-century church.